Women’s sexual health improvement: sexual quality of life and pelvic floor muscle assessment in asymptomatic women - Baszak-Radomańska, Ewa; Wańczyk-Baszak, Jadwiga; Paszkowski, Tomasz (Frontiers in Medicine, 2024)
Introduction Problems related to the quality of sexual life in gynecological practice are usually neglected. This study aimed to highlight the significance of this area of concern and evaluate the usefulness of tools, such as patient-reported outcomes (PROs) and pelvic floor examination, to improve women’s sexual wellbeing and to identify predictors of poor quality of sexual life during the well-woman annual visit. Methods A cross-sectional study was designed to examine 300 healthy women to determine whether the sexual quality of life (SQOL) questionnaire (on electronic devices) and pelvic floor muscle assessment (the vulva, anus, muscles, and periurethral (VAMP) protocol) of asymptomatic women during the annual bimanual examination (BME) help differentiate patients who would benefit from discussing sexual problems with a gynecologist. Dyspareunia was an exclusion criterion. Results The majority of subjects experienced high sexual wellbeing (82.0% with SQOL score of ≥84), with a mean of 85.7 points. SQOL scores were lower for psychiatric disorders or symptoms (37.0% of subjects), although they did not correlate with age, BMI, parity, contraception use, history of vulvovaginal symptoms, neurosurgical/orthopedic problems, and rectal, bowel, or bladder symptoms. Patients with dyspareunia (16.0% of participants, although they denied it during the face-to-face consultation) had a 3.6 times higher prevalence of low or moderate quality of sexual life. The VAMP protocol score was low in asymptomatic women, 33.0% met positive criteria (VAMP+, NRS ≥3) for pelvic floor dysfunction (overactivity), although at borderline levels. VAMP+ was positively correlated with chronic pain and genitourinary symptoms, but neither with dyspareunia nor incontinence, and was unrelated to the SQOL score (p = 0.151). Conclusion Women’s sexual health is a global health priority. Finding a way to start a discussion with an asymptomatic patient is crucial to increasing patients’ interest in disclosing a sexual health problem to be resolved. PROs or simple questions about sexual wellbeing direct the discussion mainly toward the at-risk group for sexual deterioration: those with mental health problems and women with dyspareunia. Dyspareunia is considered a predictor of decreased quality of sexual life, a major sexual disorder that should not be overlooked. Gynecological consultation should resolve concerns, identify the problem, and refer for professional sexual care if still needed.